2008
DOI: 10.1111/j.1582-4934.2008.00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for developing multi‐epitope, subunit‐based, chemically synthesized anti‐malarial vaccines

Abstract: An anti-malarial vaccine against the extremely lethal Plasmodium falciparum is desperately needed. Peptides from this parasite's proteins involved in invasion and having high red blood cell-binding ability were identified; these conserved peptides were not immun genic or protection-inducing when used for immunizing Aotus monkeys. Modifying some critical binding residues in these high-activi binding peptides' (HABPs') attachment to red blood cells (RBC) allowed them to induce immunogenicity and protection again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 111 publications
(207 reference statements)
2
50
0
Order By: Relevance
“…3a). Such results are relevant since previous studies have shown that specific structural modifications made on a-helical HABPs have been able to induce protective immune responses in Aotus monkeys when immunized with these modified merozoite HABPs Patarroyo et al 2008a).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…3a). Such results are relevant since previous studies have shown that specific structural modifications made on a-helical HABPs have been able to induce protective immune responses in Aotus monkeys when immunized with these modified merozoite HABPs Patarroyo et al 2008a).…”
Section: Discussionmentioning
confidence: 73%
“…to produce a protective immune response against P. falciparum challenge in the Aotus model (Cifuentes et al 2009;Patarroyo et al 2008a;Patarroyo and Patarroyo 2008). Complete CelTOS and TRSP sequences have been finely mapped using HeLa and (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our institute has thus adopted a functional approach towards resolving this problem by only working with molecules which have been shown to fulfil highly relevant roles in parasite invasion and by only including attractive candidates as potential components of a new, fully-protective, antimalarial vaccine (as suggested by the title of this manuscript). Such vaccine's activity must be directed against Furthermore, chemically-synthesised peptides' amino acid sequences can be easily modified to produce analogues able to modulate an immune response, leading to much more potent vaccines being obtained, as has been thoroughly shown by us at the merozoite stage where a large number of structurally-modified, biologically-relevant peptides have been able to induce fully-protective immunity in some monkeys against the most stringent challenge (the intravenous inoculation of a 100% infective strain) [5,14,16,71]. Additionally, 15-20 amino acid-long peptides are able to mimic the three-dimensional (3D) structure of the native protein from which they have been derived [16], and 3D structure of modified peptides correlates with the major histocompatibility class IIpeptide complex formation.…”
Section: Synthetic Peptides In Antimalarial Vaccine Designmentioning
confidence: 98%
“…This has led to the following specific in-house rules having been honed over more than twelve years intensive work: F R; W Y; L H; I N; P D; M K; C T or V; Q E; A S [5,14,84,85].…”
Section: Recognising and Characterising Protein Binding Sequences: Idmentioning
confidence: 98%
See 1 more Smart Citation